2022
DOI: 10.3390/bs12010016
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Usage, Working Memory, and Depression: An Experimental Investigation among University Students

Abstract: Social media usage (SMU) and its relationship with working memory (WM) and academic performance remain unclear, and there is a lack of experimental evidence. We investigated whether WM mediates the association between SMU and academic performance, including the roles of depression, anxiety, and disordered social media use as possible contributors. A sample of 118 undergraduate students aged 19 to 28 from Saudi Arabia performed a WM test twice; for one assessment, participants were required to interact with soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Our studies presented the prevalence of social media addiction and its effect on academic performance and working memory among undergraduate students. Utilization of social media differed based on the characteristics of the participants such as age, gender, and geography [34]. Meng et al, [35] reported an increasing trend in global social media addiction that can be observed among the participants in this study, as most of the students were international students.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Our studies presented the prevalence of social media addiction and its effect on academic performance and working memory among undergraduate students. Utilization of social media differed based on the characteristics of the participants such as age, gender, and geography [34]. Meng et al, [35] reported an increasing trend in global social media addiction that can be observed among the participants in this study, as most of the students were international students.…”
Section: Discussionmentioning
confidence: 60%
“…Students were scored based as follows; strongly agree (5), agree (4), neutral (3), disagree (2), and strongly disagree (1). The criteria for rating the performance were excellent (33)(34)(35)(36)(37)(38)(39)(40), good (25)(26)(27)(28)(29)(30)(31)(32), moderate (17)(18)(19)(20)(21)(22)(23)(24), poor (9)(10)(11)(12)(13)(14)(15)(16), and failing (0-8).…”
Section: Evaluation Tools and Techniquesmentioning
confidence: 99%
“…With these considerations in mind, in a study by Almarzouki et al, the relationship between compulsive social media use and educational outcomes was examined, focusing on Working Memory (WM) and accounting for depression, anxiety, and inappropriate use. Among moderately depressed adults, social media use predicted more errors compared to control conditions, though WM scores did not significantly differ 55 . Higher Social Media Disposition Scale (SMDS) scores correlated with prolonged social media use and increased depression, but WM performance and social media use did not predict Grade Point Average (GPA) scores.…”
Section: Stieger and Wunderl 28mentioning
confidence: 63%
“…Social media's impact on cognitive function 9 , educational attainment 10 , and Researchers, families, and health professionals are all interested in mental health, particularly among youths 11 . However, the majority of the research lacks scientific support and is founded on correlation and self-reporting studies 12 .…”
Section: Introductionmentioning
confidence: 99%
“…There are many theoretical models of working memory, such as cognitive and neurobiological models [ 8 ] and the cognitive resource fixed model [ 9 ]. The most authoritative theoretical model of working memory is Baddeley’s [ 5 ], which has led to controversies on the influencing factors, processing, and training methods [ 10 ].…”
Section: Introductionmentioning
confidence: 99%